2004
DOI: 10.1002/adem.200405151
|View full text |Cite
|
Sign up to set email alerts
|

Porous TiNi Biomaterial by Self‐Propagating High‐Temperature Synthesis

Abstract: Porous TiNi shape‐memory alloy (TiNi SMA) bodies with controlled pore structure were produced from the (Ti+Ni) powder mixture by self‐propagating high‐temperature synthesis (SHS) method. The effect of processing variables such as the kind of starting powders, ignition temperature and preheating schedule on the behavior of combustion wave propagation, the formation of phases and pore structure was investigated. The relationship between pore structure and mechanical properties was also investigated. An in vivo t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…15 No apparent adverse reaction was seen on or around the implant area in proximal tibia of rabbit after 6 weeks, and the ingrown bone has similar properties to the surrounding bone. 16 Shin et al 17 histomorphometrically compared a noncoated threaded zirconia implant vs a noncoated threaded titanium implant in a rabbit model. They concluded that titanium implants and zirconia implants share a similar degree of bone to implant contact, though titanium implants have a higher amount of bone between the threads as compared to zirconia.…”
Section: Rabbits As Animal Models In Contemporary Implant Biomaterialmentioning
confidence: 99%
“…15 No apparent adverse reaction was seen on or around the implant area in proximal tibia of rabbit after 6 weeks, and the ingrown bone has similar properties to the surrounding bone. 16 Shin et al 17 histomorphometrically compared a noncoated threaded zirconia implant vs a noncoated threaded titanium implant in a rabbit model. They concluded that titanium implants and zirconia implants share a similar degree of bone to implant contact, though titanium implants have a higher amount of bone between the threads as compared to zirconia.…”
Section: Rabbits As Animal Models In Contemporary Implant Biomaterialmentioning
confidence: 99%
“…When a pressed pellet of mixed Ni and Ti powders is heated and ignited at one edge [14,15,[22][23][24][25][26][27][28], porous NiTi is created in a reaction wave propagating traveling through the pellet through self-propagating high-temperature synthesis (SHS), as previously studied for numerous other intermetallics [29]. Mostly-open porosity in the range 45-65% is achieved, with a 120-600 lm pore size.…”
Section: Introductionmentioning
confidence: 98%
“…[4]. Powder metallurgy techniques used for creating porous NiTi include partial powder sintering [16][17][18][19][20][21][22][23][24][25], transient liquid phase sintering [26,27], expansion of argon entrapped during hot isostatic pressing (HIP) of powders [28][29][30][31], self-propagating high-temperature synthesis (SHS) [7,[32][33][34][35][36][37][38], metal injection molding (MIM) followed by sintering or SHS [39,40], and combinations of these techniques with various space-holder materials. Also, laser engineered net shaping (LENS) [41] and selective laser sintering (SLS) [42,43] have recently been employed to fabricate NiTi scaffolds from powders.…”
Section: Introductionmentioning
confidence: 99%
“…Of the above bulk metallic implant materials for loadbearing implant applications, NiTi has the lowest Young's modulus (68 GPa [6]) and is thus particularly suitable for reducing stress-shielding. Porous NiTi has previously been fabricated [7,8] with average stiffness values as low as that of cortical bone (12)(13)(14)(15)(16)(17) or even cancellous bone (<3 GPa) [9].…”
Section: Introductionmentioning
confidence: 99%